Analysis of Factors that Influence Consumer Behavior towards Shopping Cart Abandonment in Online Shopping at Shopee - Putri, Salwa Az Zhahra; Rusdianto, Yuniardi (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to identify and analyse factors that influence shopping cart abandonment behaviour when shopping on the Shopee marketplace. This research uses a purposive sampling technique of 100 active students in the Surabaya with the analytical method used in this research is multiple linear regression analysis. From the results of the analysis carried out, it was found that simultaneously (F test) the variables emotional ambivalence, hesitation at checkout, payment intention, choice overload, compare with website, perceived transaction inconvenience, perceived cost, and perceived risk had a significant effect on shopping cart abandonment behaviour. when shopping on the Shopee marketplace. Meanwhile, partial testing (t test) shows that choice overload is a variable that significantly influences shopping cart abandonment behaviour in online shopping at Shopee.